Determinan Pengadopsian Layanan Internet Banking: Perspektif Konsumen Perbankan Daerah Istimewa Yogyakarta - Hadri Kusuma; Dwi Susilowati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
The consumer adoption of a new information system technology has been a central theme in information systems research nowadays. Prior research on this area has identified several factors influencing end user acceptance and satisfaction. Using the Technology Acceptance Model (TAM), this research investigated end consumer perceptions of Internet Banking services in relation to determinants of the services. The findings indicated that alliance service, task familiarity, and perceived ease of use are the main factors of the adoption. Keywords: technology acceptance model, internet banking, personalisasi, jasa aliansi, kefamiliaran tugas, kemam¬puan akses, persepsi manfaat, persepsi kemudahan penggunaan, sikap.